DETERMINANTS OF INVESTMENT BEHAVIOUR – A STUDY WITH SPECIAL REFERENCE TO GOVERNMENT HIGHER SECONDARY SCHOOL TEACHERS IN THIRUVANANTHAPURAM DISTRICT - A, Mubarak S; Farveen, H Sabeena (International Journal of Psychosocial Rehabilitation, 2020)
The selection of investment would depend on the specific need, rate of return and risk preference and the degree of risk and return varies for different investment avenues. The aim of Investment is to multiply the money at various rates depending upon the term of the investment. An investor can choose from a variety of funds to suit his risk tolerance, various investment avenues and objectives. Against this background, the researcher has taken up this topic. Investors are finding various problems in selecting their various investment avenues. It is identified that there is a need for research work in the field of investment behavior of government higher secondary school teachers in Thiruvananthapuram district. It is concluded that in Thiruvananthapuram district government higher secondary school teachers prefer to invest in land, buildings, and bank deposits but they do not prefer forex trading, equity shares, mutual fund, government bond and debenture. All the age groups give more importance to invest in land, buildings, insurance, and bank deposits. In Thiruvananthapuram district government higher secondary school teachers are more aware about various investment avenues like insurance, bank deposits, small savings like post office savings etc.